Pemasaran Relasional Berdasarkan Model Enam Pasar di Kelompok Tani Cipta Mandiri - Juniar, Rossa; Sadeli, Agriani Hermita (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The vegetables demand increasing is an opportunity for producers to gain sell their harvest. relational marketing oriented towards long-term relationships implementation can retain consumers  to create customer loyalty. Therefore, this research aims to find out and describe how relational marketing process in the Cipta Mandiri Farmer Group in Cibengang Village, Ciburial Village, Bandung, West Java with the stakeholders involved based on the six market models. This research uses a qualitative design. The Cipta Mandiri Farmer Group has relationships with each market from the six-market model, namely the customer market (end consumers, the Agritektur, intermediary and traditional markets), supplier market (Buana Tani and Tani Sugih), influence market (landowners, Creative Net, courier Punten distributors, and Agritektur), referral market (consumers, Creative Net and Agritektur), recruitment market (labor from surrounding villages), and internal market (people involve in management). Regular and intensive communication should be carried out between the Cipta Mandiri farmer group and stakeholders to maintain good relational marketing.